Systematic Review: Analysis of the Impact of Hydrated Lime (Cao) Exposure pon Coal Mining Workers - Sri, Dwi Irma Mayang; Windusari, Yuanita; Sunarsih, Elvi (Journal La Medihealtico, 2024)
This study aims to analyze the effects of quicklime (CaO) exposure on the health of coal mine workers. Quicklime is frequently used in the treatment of mine pit water to neutralize acidity and precipitate heavy metals. However, its use also poses potential health risks to workers who are exposed to it. This study involved measuring the levels of quicklime exposure at various mine locations and evaluating its health impacts on workers through health surveys, lung function tests, and blood analyses. The results indicate that long-term exposure to quicklime can cause irritation of the respiratory tract, eyes, and skin. Workers exposed to high doses exhibited symptoms such as chronic cough, shortness of breath, and dermatitis. Laboratory analyses revealed increased calcium levels in the blood, although still within normal limits. Factors such as exposure duration, use of personal protective equipment (PPE), and working conditions significantly influenced the level of health risk. These findings highlight the importance of implementing strict occupational safety protocols, including adequate PPE use and regulation of quicklime exposure, to minimize health risks for coal mine workers. Additionally, regular monitoring and occupational health programs need to be enhanced to ensure the well-being of workers in coal mining environments.